A system of nonsmooth equations solver based upon subgradient method - Long, Q.; Wu, Changzhi; Wang, Xiangyu (Elsevier Inc., 2015)
In this paper, a subgradient method is developed to solve the system of (nonsmooth) equations. First, the system of (nonsmooth) equations is transformed into a nonsmooth optimization problem with zero minimal objective function value. Then, a subgradient method is applied to solve the nonsmooth optimization problem. During the processes, the pre-known optimal objective function value is adopted to update step sizes. The corresponding convergence results are established as well. Several numerical experiments and applications show that the proposed method is efficient and robust.